MODELING AND SIMULATION OF THE ORTHOGONAL CUT BY USING THE LAW OF DAMAGE - Himed, Lynda (European Scientific Journal, ESJ, 2014)
The principal objective of our work is to simulate the orthogonal cutting process a computer code by the finite element method which is ABAQUS by its explicit integration diagram and by quoting the method of the adaptive grid (ALE) and the law of Johnson- Cook behavior established in ABAQUS. This study is carried out for a steel of the 42CD4 type and a tool of which the angle of cut is 6°. The tool has a presumedly rigid.